Understanding the Oral Health-Related Quality of Life of the Geriatric Population in Tribal Setting in Jharkhand-A Pilot Study - Mohan, Sumit; Kumar, Gaurav; Priyank, Harsh; Viswanath, Butta (Indian journal of community medicine, 2025)
The aim of this descriptive cross-sectional household pilot study is to assess the oral health-related quality of life (OHRQoL) using General Oral Health Assessment Index (GOHAI) in the geriatric tribal population of Jharkhand, India. This analysis comprised 200 study participants of which 89 were males, while 111 were females. The subjects were interviewed on a 12-point GOHAI questionnaire to assess the physical functions, psychological aspects, and presence or absence of dental diseases and assessed on a 6-point Likert scale. The study results showed that the majority of the participants seldom faced problems in swallowing and speaking. On assessing OHRQoL, the male population was found to have better GOHAI score (34.991) as compared to females (10.200). This study revealed the presence of increased severity of dental disease and poor perception of oral health among the tribal population due to lack of knowledge and poor availability of dental healthcare facilities.